microRNAs: Emerging Targets Regulating Oxidative Stress in the Models of Parkinson's Disease - Xie, Yangmei; Chen, Yinghui (Frontiers in Neuroscience, 2016)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder. This chronic, progressive disease is characterized by loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) and the presence of cytoplasmic inclusions called Lewy bodies (LBs) in surviving neurons. PD is attributed to a combination of environment and genetic factors, but the precise underlying molecular mechanisms remain elusive. Oxidative stress is generally recognized as one of the main causes of PD, and excessive reactive oxygen species (ROS) can lead to DA neuron vulnerability and eventual death. Several studies have demonstrated that small non-coding RNAs termed microRNAs (miRNAs) can regulate oxidative stress in PD. Relevant miRNAs involved in oxidative stress can prevent ROS-mediated damage to DA neurons, suggesting that specific miRNAs may be putative targets for novel therapeutic targets in PD.